2010
DOI: 10.4103/0259-1162.73513
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction in anesthesia: A modified Iowa Satisfaction in Anesthesia Scale

Abstract: Objectives:To set up and validate a patient satisfaction questionnaire based on Iowa Satisfaction in Anesthesia Scale (ISAS) for evaluating the degree of patient satisfaction in anesthesia.Materials and Methods:We established and validated a survey questionnaire of 13 questions measuring the following dimensions adequacy of patient information; participation in decision making, nurse patient relation, accessibility of communication with the anesthesiologist, patient fear and anxiety and the post anesthesia car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 21 publications
2
18
0
2
Order By: Relevance
“…Of patients who operated upon under general anesthesia and local anesthesia, 87 % of patient was satisfied, 0.5 % dissatisfied and 12.5 % had no opinion [ 13 ]. Whereas another study revealed that 54 % of patients achieved an overall satisfaction less than 85 %, and female, educated and American Society of Anesthesiologists physical status (ASA) 1–2 patients were less satisfied [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of patients who operated upon under general anesthesia and local anesthesia, 87 % of patient was satisfied, 0.5 % dissatisfied and 12.5 % had no opinion [ 13 ]. Whereas another study revealed that 54 % of patients achieved an overall satisfaction less than 85 %, and female, educated and American Society of Anesthesiologists physical status (ASA) 1–2 patients were less satisfied [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…We decided not to use the Leiden Perioperative care Patient Satisfaction questionnaire because in our opinion it was too lengthy to use during a structured interview [10]. Many of the previously published studies involved staff distributing the questionnaires to the patients at the ward, resulting in response rates between 80 and 100% [10][11]. To improve the response rate, we conducted systematic, structured interviews using our qu-estionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…This tool has been shown useful in monitored anesthesia care associated with anesthetic techniques for several other procedures, including cataract surgery, emergency medical procedures, hernia repair, craniotomy, and transesophageal echocardiography; it has been validated in several languages . Within otolaryngology, it has recently been used in the context of local anesthesia for cochlear implantation and in‐office lateral nasal wall block for office‐based procedures, although the small numbers in these series seem to have precluded further reliability and validity testing and any group comparisons.…”
Section: Discussionmentioning
confidence: 99%